2005
DOI: 10.1007/s00125-005-1893-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of left ventricular hypertrophy in the reduction of endpoints in NIDDM with the angiotensin II antagonist losartan (RENAAL) study

Abstract: Aims/hypothesis: We explored the impact of baseline left ventricular hypertrophy (LVH) and losartan treatment on renal and cardiovascular (CV) events in 1,513

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…17 Many studies have sought to understand the pathophysiology of kidney -heart interaction by investigating the impact of renal function on LVH, but few have investigated from the opposite point of view. 8, 9 In the present study, conducted as a subanalysis of the CASE-J trial, we found that renal function improved under strict BP control, and that its improvement in high-risk hypertensive patients was greater in patients without LVH than in those with LVH. LVH is an adaptive response that reduces LV wall stress against volume and pressure overload.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…17 Many studies have sought to understand the pathophysiology of kidney -heart interaction by investigating the impact of renal function on LVH, but few have investigated from the opposite point of view. 8, 9 In the present study, conducted as a subanalysis of the CASE-J trial, we found that renal function improved under strict BP control, and that its improvement in high-risk hypertensive patients was greater in patients without LVH than in those with LVH. LVH is an adaptive response that reduces LV wall stress against volume and pressure overload.…”
Section: Discussionsupporting
confidence: 52%
“…10 In contrast, Boner et al reported that LVH was associated with a significantly increased risk of not only CV events but also the progression of kidney disease in patients with type 2 diabetes and nephropathy. 9 Of 4,703 patients in the CASE-J trial, only 46 (1.0%) experienced a renal event, a much smaller proportion than the 32.9% in the RENALL study, indicating that the CASE-J trial lacked sufficient statistical power to evaluate the impact of LVH on renal events.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…especially poor prognosis (Boner et al, 2005;Struthers & Morris, 2002;Valensi et al, 1997). Emerging evidence has implicated the diabetic milieu of hyperinsulinemia, insulin resistance, hyperglycemia, and increased non-esterified fatty acids in the pathophysiology of LVH in DM patients.…”
Section: Cardiomyopathies -From Basic Research To Clinical Managementmentioning
confidence: 99%
“…In a new analysis of the data from the Reduction of Endpoints in NIDDM with Angiotensin II Antagonist Losartan study [32], using the LIFE criteria for LVH, i.e. based on electrocardiographic findings [33], 12% of patients with type 2 diabetes with overt proteinuria were found to have LVH.…”
Section: Left Ventricular Hypertensionmentioning
confidence: 99%